State-level differentials in COVID-19 fatality: exploring age and sex disparities in Malaysia’s pandemic experience - Teh, Jane Kimm Lii *; Teo, Kok Lay *; Bradley, D.A. *; Chook, Jack Bee *; Ang, Woo Teck *; Peh, Suat Cheng * (Springer, 2024)
Issue COVID-19 has resulted in mortality worldwide and exposed vulnerabilities in public health systems. Although countries have since transitioned to the endemic phase, it is nonetheless important to identify inequities within populations to improve public health strategies in light of another health crisis.